Self-assembled monomolecular layer material based on carbazole derivative as well as preparation method and application of self-assembled monomolecular layer material

By using self-assembled monolayer materials based on carbazole derivatives, the complexity and stability issues of hole transport materials in perovskite solar cells were solved, achieving high-efficiency photoelectric performance and improved stability, with cell efficiency reaching 26.23-26.15%.

CN121378338APending Publication Date: 2026-01-23HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511731271.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

The synthesis of hole transport materials in existing perovskite solar cells is complicated and costly, and additives can lead to device instability. The traditional hole transport layer is thick, which introduces interfacial recombination resistance. Existing SAM materials do not meet the commercialization requirements in terms of molecular structure, energy level matching and interfacial contact characteristics.

Method used

By employing carbazole derivative-based self-assembled monolayer materials, an asymmetric functional substrate is constructed by introducing aromatic rings, which enhances the molecular dipole moment, promotes π-π stacking interactions, and forms a highly ordered self-assembled monolayer, thus optimizing film formation and interfacial hole transport.

Benefits of technology

The device's photoelectric performance and stability were improved, with a cell efficiency of 26.23-26.15%, a short-circuit photocurrent density of 26.29-26.34 mA cm⁻², an open-circuit voltage of 1.167-1.179 V, and a fill factor of 0.8432-0.8531.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121378338A_ABST
    Figure CN121378338A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite solar cells, and particularly relates to a self-assembled monomolecular layer material based on carbazole derivatives and a preparation method and application thereof. An aromatic ring is additionally introduced to a carbazole molecular skeleton to construct a functional molecular substrate with an asymmetric planar configuration, so that the molecular dipole moment is enhanced, and ordered accumulation among molecules is promoted. Meanwhile, due to the introduction of different aromatic ring groups, the molecular energy level can be effectively optimized, the solubility and film-forming quality of the material can be improved, and the interface contact characteristic of a device can be regulated and controlled, so that the interface hole transport and extraction efficiency can be improved. The perovskite solar cell based on the self-assembled monomolecular layer achieves photoelectric conversion efficiency exceeding 26%, and shows excellent long-term operation stability. The research provides an innovative interface material design strategy for developing an efficient and stable perovskite solar cell, and has an important application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of perovskite solar cells, and relates to the preparation of an organic semiconductor material, in particular to application of a self-assembled monolayer material of a carbazole derivative in a perovskite solar cell BACKGROUND

[0002] As a new generation of photovoltaic technology, perovskite solar cells have attracted much attention due to their high efficiency and low cost. In its structure, the hole transport layer is crucial for extracting and transporting photo-generated holes and suppressing charge recombination, and is the core that determines the performance and stability of the cell. The widely used hole transport material, such as Spiro-OMeTAD, can achieve high efficiency, but has significant defects: first, the synthesis and purification steps of the material are complicated and costly; second, in order to achieve high conductivity, hygroscopic dopants must be added, which can accelerate the decomposition of the perovskite layer, seriously damage the long-term stability of the device, and lead to uneven performance. In addition, the traditional hole transport layer usually has a thickness of tens of nanometers, which not only increases the consumption of materials, but also may introduce a higher interface recombination resistance.

[0003] To overcome the above bottlenecks, self-assembled monolayer materials have emerged as a promising alternative. SAM materials form a dense, ultra-thin monolayer on the substrate surface through their terminal anchoring groups, with a thickness of only 1-2 nanometers. This ultra-thin structure is conducive to the efficient extraction and transmission of charges, and can also achieve better energy level alignment. More importantly, SAM materials usually do not need chemical doping to obtain sufficient conductivity, which fundamentally avoids the stability problems caused by additives. However, the SAM materials in the prior art still need to be optimized in terms of molecular structure, energy level matching, film quality, and interface contact characteristics with the perovskite layer, and their comprehensive performance has not yet met the requirements of commercial application. Therefore, developing new and efficient SAM hole transport materials is of urgent industrial demand and great technical value for promoting perovskite solar cells to practical applications. SUMMARY

[0004] In view of the deficiencies of the prior art, the first object of the present application is to provide a self-assembled monolayer material based on a carbazole derivative, which introduces an aromatic ring on the basis of carbazole to construct an asymmetric functional substrate, enhance the molecular dipole moment, and promote the intermolecular π-π stacking interaction, thereby inducing the formation of a highly ordered self-assembled monolayer. At the same time, through the optimization of the aromatic ring structure, the solubility and film-forming property of the molecule are improved, the transport and separation of interface holes are increased, and the photovoltaic performance of the device is effectively improved; the second object of the present application is to provide a preparation method of the material; and the third object of the present application is to provide application of the material in a perovskite solar cell.

[0005] The application is realized by the following technical scheme: A self-assembled monolayer material based on carbazole derivatives has the chemical structural formula as shown below: .

[0006] The further improved scheme of the application is: A preparation method of a self-assembled monolayer material based on carbazole derivatives comprises the following steps: (1) taking a benzocarbazole compound AH as an initial raw material, and allowing the initial raw material to react with 1.4-dibromobutane to generate a compound B through a substitution reaction; (2) allowing the compound B to react with triethyl phosphite to generate a compound C through a substitution reaction; (3) allowing the compound C to generate a final product D through a hydrolysis reaction; The synthesis route is shown as follows:

[0007] The initial raw material benzocarbazole compound AH is selected from the following compounds: .

[0008] The still further improved scheme of the application is: The specific operation of step (1) is to uniformly stir and mix the compound AH, 1.4-dibromobutane, tetrabutylammonium bromide, potassium hydroxide and water, and allow the mixture to react at 50-80 DEG C for 5-8 h to generate the compound B.

[0009] Further, in step (1), the molar ratio of the compound AH, 1.4-dibromobutane, tetrabutylammonium bromide and potassium hydroxide is 1:18-21:0.01-0.12:10-12; and the dosage ratio of the potassium hydroxide to water is 1 g:0.1-1.2 mL.

[0010] Further, the specific operation of step (2) is to dissolve the compound B in triethyl phosphite under the protection of argon, and allow the mixture to react at 150-180 DEG C for 10-15 h to generate the compound C.

[0011] Further, in step (2), the molar ratio of the compound B to triethyl phosphite is 1:12-20.

[0012] Further, the specific operation of step (3) is to dissolve the compound C and trimethylsilyl bromide in 1.4-dioxane under the protection of argon, and allow the mixture to react at room temperature for 12-18 h, and remove the solvent through reduced pressure distillation. The obtained solid is added into methanol and water, and the mixture is continuously reacted for 2-5 h, and the solid is filtered and dried to obtain the compound D.

[0013] Further, in step (3), the molar ratio of the compound C to trimethylsilyl bromide is 1:7-11.

[0014] A further improvement of the present application is: The application of the self-assembled monolayer material based on the carbazole derivative in a perovskite solar cell.

[0015] Compared with the prior art, the present application has the following beneficial effects: 1. The self-assembled monolayer material provided by the present application introduces an aromatic ring on the basis of carbazole, constructs an asymmetric functional substrate, enhances the molecular dipole moment, and can realize more ordered self-assembled monolayers. In addition, through optimization of the aromatic ring structure, the solubility and film-forming property of the molecules are improved, the energy level matching is adjusted, the transport and separation performance of the interface holes are enhanced, and thus the photoelectric performance and stability of the device are improved.

[0016] 2. The application of the self-assembled monolayer organic semiconductor material as a hole transport layer in a perovskite solar cell provided by the present application, test results show that: the short-circuit photocurrent density of the battery device reaches 26.34 mA cm -2 , the open-circuit voltage is 1.167 V, the fill factor (FF) is 0.8531, and the photoelectric conversion efficiency reaches 26.23%, which has practical significance for improving the efficiency of perovskite solar cells. BRIEF DESCRIPTION OF DRAWINGS

[0017] Figure 1 The nuclear magnetic resonance spectrum of the compound of formula 4 prepared by the present application is shown in the following figure: Figure 2 The nuclear magnetic resonance spectrum of the compound of formula 8 prepared by the present application is shown in the following figure: Figure 3 The J-V curve of the perovskite solar cell prepared by the compound of formula 4 prepared by the present application as a self-assembled monolayer is shown in the following figure: Figure 4 The J-V curve of the perovskite solar cell prepared by the compound of formula 8 prepared by the present application as a self-assembled monolayer is shown in the following figure. DETAILED DESCRIPTION

[0018] The present application will be described in detail below in combination with specific embodiments.

[0019] Example 1: Preparation of compound 4

[0020] The synthesis route is as follows:

[0021] (1) Synthesis of compound of formula 2: Into a 100 mL two-necked flask, compound 1 (3 g, 9 mmol), 1,4-dibromobutane (21.5 mL, 177.24 mmol), tetrabutylammonium bromide (60 mg, 0.18 mmol), potassium hydroxide (5.5 g, 98.21 mmol) and water (5.5 mL) were added successively. The mixture was heated to 70 °C and refluxed for 6 h. After the reaction mixture was cooled to room temperature, dichloromethane and water were added for extraction. The organic phase was distilled under reduced pressure. The crude product was purified by column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 ~ 10 / 1) to obtain 3.5 g of white solid with a yield of 82 %.

[0022] (2) Synthesis of compound of formula 3: Into a 100 mL two-necked flask, compound 2 (3.4 g, 7.27 mmol) and triethyl phosphite (25 mL, 144.89 mmol) were added successively under argon atmosphere. The reaction mixture was heated to 165 °C and reacted for 12 h. After the reaction mixture was cooled to room temperature, the excess triethyl phosphite was distilled off under reduced pressure. The crude product was purified by column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 ~ 1 / 4) to obtain 3.6 g of white solid with a yield of 94.7 %.

[0023] The structural characterization data of compound of formula 3 are as follows: 1 H NMR (400 MHz, DMSO) δ 8.88 (d, J = 8.4 Hz, 1H), 8.71 (d, J = 8.4Hz, 1H), 8.09 (dd, J = 8.1, 1.4 Hz, 1H), 7.99 (s, 2H), 7.91 – 7.82 (m, 2H),7.74 (ddd, J = 8.4, 6.8, 1.5 Hz, 1H), 7.65 – 7.58 (m, 1H), 7.51 (t, J = 7.5Hz, 1H), 7.35 (dd, J = 6.2, 2.8 Hz, 2H), 4.88 (t, J = 8.0 Hz, 2H), 3.92 (ddd, J = 8.5, 7.0, 1.9 Hz, 4H), 1.76 (s, 12H), 1.16 (t, J = 7.0 Hz, 6H). (3) Synthesis of compound of formula 4: Into a 100 mL two-necked flask, compound 3 (3.4 g, 6.47 mmol), bromotrimethylsilane (7 mL, 53.98 mmol) and 15 mL 1,4-dioxane were added successively under argon atmosphere. The mixture was stirred at room temperature for 18 h. The solvent was removed by distillation under reduced pressure. The obtained solid was added successively with 15 mL methanol and 30 mL deionized water. The mixture was stirred for 3 h. The white solid was obtained by filtration and washed with water. The yield was 2.7 g, 89.1%.

[0024] The structural characterization data of compound 4 are as follows: 1 H NMR (400 MHz, DMSO) δ 8.89 (d, J = 8.4 Hz, 1H), 8.73 (d, J = 8.2Hz, 1H), 8.10 (d, J = 8.1 Hz, 1H), 8.00 (s, 2H), 7.95 – 7.86 (m, 2H), 7.74(t, J = 7.7 Hz, 1H), 7.68 – 7.58 (m, 1H), 7.51 (t, J = 7.5 Hz, 1H), 7.39 –7.32 (m, 2H), 4.98 – 4.77 (m, 2H), 1.86 – 1.55 (m, 12H). Example 2

[0025]

[0026] The synthesis route is as follows:

[0027] (1) Synthesis of compound 6: Into a 100 mL two-necked flask, compound 5 (3 g, 11.22 mmol), 1,4-dibromobutane (27 mL, 222.58 mmol), tetrabutylammonium bromide (400 mg, 1.24 mmol), potassium hydroxide (6.9 g, 123.21 mmol) and water (6.9 mL) were added successively. The mixture was heated to 70 °C and refluxed for 6 h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction. The organic phase was distilled under reduced pressure. The crude product was purified by column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1~10 / 1) to obtain a white solid 3.3 g with a yield of 73 %.

[0028] (2) Synthesis of compound 7: To a 100 mL two-necked flask, compound 6 (3.3 g, 8.2 mmol) and triethyl phosphite (17 mL, 98.52 mmol) were added successively under argon atmosphere. The reaction was heated to 165 °C for 12 h. After the reaction was cooled to room temperature, the excess triethyl phosphite was distilled out under reduced pressure. The crude product was purified by column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 ~ 1 / 4) to give a white solid 3.5 g, yield 93 %.

[0029] (3) Synthesis of compound 8: To a 100 mL two-necked flask, compound 7 (3.5 g, 7.61 mmol), bromotrimethylsilane (10 mL, 77.12 mmol) and 15 mL 1,4-dioxane were added successively under argon atmosphere. The mixture was stirred at room temperature for 18 h. The solvent was removed under reduced pressure. The obtained solid was added successively with 15 mL methanol and 30 mL deionized water. The solid was precipitated by stirring for 3 h. The white product 2.87 g was obtained by filtration and water washing, yield 93 %.

[0030] The structural characterization data of compound 8 are as follows: 1 H NMR (400 MHz, DMSO) δ 8.96 (d, J = 8.3 Hz, 1H), 8.82 (d, J = 8.9Hz, 1H), 8.66 (d, J = 8.6 Hz, 1H), 8.19 – 8.07 (m, 3H), 7.99 (d, J = 9.0 Hz,1H), 7.85 (d, J = 8.7 Hz, 1H), 7.74 (tdd, J = 8.8, 6.9, 1.4 Hz, 2H), 7.61(ddd, J = 7.9, 6.8, 0.9 Hz, 1H), 7.53 (ddd, J = 8.0, 6.9, 1.0 Hz, 1H), 5.05(t, J = 7.4 Hz, 2H), 2.07 (p, J = 7.6 Hz, 2H), 1.81 – 1.52 (m, 4H). Example 3

[0031] The nuclear magnetic resonance spectrum of compound 4, a self-assembled monolayer material prepared in Example 1, is as follows:Figure 1 The present embodiment provides a compound of formula 20 prepared in Example 1, which is used to prepare a perovskite solar cell according to the method in the literature: G. Qu; S. Cai; Y. Qiao; et al. Joule, 2024, 8, 2123-2134. The test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), and the data acquisition uses Keithley 2400 digital source meter. The test results are shown in Figure 3 The short-circuit photocurrent density of the battery device reaches 26.34 mA cm -2 The open-circuit voltage is 1.167 V, the fill factor (FF) is 0.8531, and the photoelectric conversion efficiency reaches 26.23%.

[0032] Example 4 The nuclear magnetic resonance spectrum of the self-assembled monolayer material compound 8 prepared in Example 2 is shown in Figure 2 The present embodiment provides a compound of formula 8 prepared in Example 2, which is used to prepare a perovskite solar cell according to the method in the literature: G. Qu; S. Cai; Y. Qiao; et al. Joule, 2024, 8, 2123-2134. The test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), and the data acquisition uses Keithley 2400 digital source meter. The test results are shown in Figure 4 The short-circuit photocurrent density of the battery device reaches 26.29 mA cm -2 The open-circuit voltage is 1.179 V, the fill factor (FF) is 0.8432, and the photoelectric conversion efficiency reaches 26.15%.

[0033] The above description of the embodiments is only for the purpose of illustrating the technical concept and characteristics of the present application, and the purpose is to enable those skilled in the art to understand the content of the present application and implement it. Those skilled in the art can easily make various modifications to these embodiments, and apply the general principles described herein to other embodiments without creative labor, therefore, the above embodiments cannot limit the protection scope of the present application. Any improvements and modifications made by those skilled in the art based on the disclosure of the present application without departing from the scope of the present application shall be covered within the protection scope of the present application.

Claims

1. A self-assembled monolayer material based on a carbazole derivative, characterized in that, The chemical structural formula is shown as follows: 。 2. The method of claim 1, wherein the self-assembled monolayer material based on a carbazole derivative is prepared by the following steps: (1) dissolving the carbazole derivative in a solvent to prepare a solution; (2) applying the solution to a substrate to form a film; and (3) drying the film. The method comprises the following steps: (1) taking an aromatic ring and carbazole compound AH as an initial raw material, and allowing the initial raw material to react with 1.4-dibromobutane to generate compound B; (2) allowing compound B to react with triethyl phosphite to generate compound C; (3) allowing compound C to undergo a hydrolysis reaction to generate final product D; The synthesis route is shown as follows: ; The initial raw material benzocarbazole compound AH is selected from the following compounds: 。 3. The method for preparing a self-assembled monolayer material based on a carbazole derivative according to claim 2, characterized in that: The specific operation of step (1) is that compound AH is uniformly mixed with 1.4-dibromobutane, tetrabutylammonium bromide, potassium hydroxide and water, and is allowed to react at 50-80 DEG C for 5-8 h to generate compound B.

4. The method of claim 3, wherein the method is characterized by: In step (1), the molar ratio of compound AH, 1.4-dibromobutane, tetrabutylammonium bromide and potassium hydroxide is 1:18-21:0.01-0.12:10-12; and the ratio of the amount of potassium hydroxide to water is 1 g:0.1-1.2 mL.

5. The method of claim 2, wherein the self-assembled monolayer material based on a carbazole derivative is prepared by the following steps: (1) dissolving the carbazole derivative in a solvent; (2) adding a base to the solution; (3) adding a metal salt to the solution; and (4) removing the solvent from the solution. The specific operation of step (2) is that compound B is dissolved in triethyl phosphite under the protection of argon, and is allowed to react at 150-180 DEG C for 10-15 h to generate compound C.

6. The method of claim 5, wherein the method is characterized by: In step (2), the molar ratio of compound B to triethyl phosphite is 1:12-20.

7. The method of claim 2, wherein the self-assembled monolayer material based on a carbazole derivative is prepared by the following steps: (1) dissolving the carbazole derivative in a solvent; (2) applying the solution to a substrate; and (3) drying the solution. The specific operation of step (3) is that compound C is dissolved in 1.4-dioxane with trimethylsilyl bromide under the protection of argon, and is allowed to react at room temperature for 12-18 h, and the solvent is removed by reduced pressure distillation, and the obtained solid is added to methanol and water, and is allowed to continue to react for 2-5 h, and the solid is separated and dried to obtain compound D.

8. The method of claim 7, wherein the method is characterized by: In step (3), the molar ratio of compound C to trimethylsilyl bromide is 1:7-11.

9. The application of the self-assembled monolayer material based on the carbazole derivative in claim 1 in a perovskite solar cell.